Analisis Pemahaman Konsep Matematis Siswa Pada Materi Matriks Kelas X IIS SMA PGRI 3 Padang - Zelin Amanda; Ramadoni Ramadoni; Alfi Yunita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
His research is motivated by students' understanding of mathematical conceptsstill low in class X IIS SMA PGRI 3 Padang. This is caused bylearning that is carried out is less interesting and understanding of mathematical conceptslow students. This study aims to find out analyzeunderstanding of mathematical concepts for class X IIS SMA PGRI 3 Padang.This type of research is a type of quantitative descriptive research. Populationin this study were all students of class X IIS SMA PGRI 3 Padang. The sampling technique was carried out by means of purposive sampling, selectedclass X IIS as the class being analyzed. The research instrument is in the form ofposttest by using an indicator of understanding the concept that functions formeasure the level of understanding of students' mathematical concepts. The average score of students' understanding of mathematical concepts in the sample classis 96 with a maximum value of 100 and a minimum value of 88 and a standard deviation3,7. It can be seen that the ability to understand mathematical concepts in the fourththe indicator of understanding the concept is the indicator restating aconcept 92%, classify objects according to certain properties according tothe concept is 46%, presenting the concept in various forms of representationmathematics 34 %, and apply concepts or logarithms to the solutionthe problem is 53%, so of the four indicators it is classified as lowthe ability to understand mathematical concepts, namely the Presenting indicatorconcepts in various forms of mathematical representation with numbersthe percentage is 34% and the highest percentage is on the indicatorrestating a concept with a total percentage of 92%.